Influence of Parents’ Background towards Their Children Education - Gitit I.P Wacana (Sintuwu Maroso Journal of English Teaching, 2017)
The aims of this research are to find out the number drop out students and to find out the cause factors of drop out students in SMPN 2 Lembo. Located of the research is 5 village area in SMPN 2 Lembo. Method used in this research is qualitative descriptive method, that is to collect data in the form of direct interview. Researcher in collecting data, first the research take data from school to find out data drop out students and direct interview of parents to find out it cause factors. Result of the interview, then so recorded. After that, the researcher write result interview to can identifying. As result from research, found there are 35 students SMPN 2 Lembo which drop out. The cause factors are: 1). Parents economic background, 2). Own decision, 3). Marriage demand and, 4). Learning incapability.Keywords: Parent’s background, children education